Penerapan Model Pembelajaran Inkuiri dalam Membaca dan Menulis Keterampilan Teks Naratif dalam Mata Pelajaran Bahasa Indonesia Kelas IV MI Nurul Huda 1 Kepatihan Gresik - Noni, Editha; Nisa, Lita Aditya Khoirun (Prodi Pendidikan Guru Sekolah Dasar, 2026)
Application of Inquiry Learning Model in Indonesian Language Subjects is a form of conscious action in activities that cultivate, shape and develop the potential of how students shape their personalities in order to develop their personalities as a whole, which is beneficial to themselves and also the environment around. The goal is for students to be skilled. The qualitative method is used in this research because it is a research procedure that produces descriptive information about people and observed behaviors in word or oral form. In fact, students in 4th grade of MI Nurul Huda 1 do not have a reading culture. Moreover, teachers only used learning material from the students worksheet, by approaching students individually and providing understanding to students.